An approach to evaluating the impact of contaminants on flux deposition in gas turbines - Mori, Stefano; Mendil, Mathilde; Wells, Jonathan; Chapman, Neil; Simms, Nigel J.; Wells, Roger; Sumner, Joy (Springer, 2026)
Gas turbines are a key part of many countries’ power generation portfolios, but components such as blades can suffer from hot corrosion attack, which can decrease component lifetimes. Corrosion is driven by impurity levels in the fuel and air (e.g., species containing sulphur and/or alkali metals) and depends on environmental conditions (e.g., air pollution, seawater droplets), that can lead to formation of harmful species in the gas. Understanding and determining the deposition flux of such contaminants is crucial for understanding the problem. Thermodynamic simulations were used to determine types and amounts of potentially corrosive contaminants, this was followed by deposition fluxes calculations. An operating scenario, based upon an offshore platform was evaluated. The effectiveness of different filtration systems has been evaluated. The impurity levels of alkali metals, such as sodium, greatly impacts the calculated deposition flux of species linked to corrosion attack. The presence of Na2SO4, and K2SO4 was found, at temperature representative of stage 2 nozzle guide vanes. Lowering sulphur input (from fuel or air) can be an efficient way to decrease deposition, attention must also be paid to lowering the amount of alkali metal entering the gas turbine, which can be lowered by the filtration systems’ correct use.
Keywords: Gas turbine; Turbine blades; Condensation; Na2SO4; Air filtration; Sea salt aerosol